Dīwān-i Qāʾimiyyāt - Kātib, Ḥasan Maḥmūd, (Miras Maktoob, ISBN: 9789004365452., 2019)
Ḥasan Maḥmūd Kātib (d. after 640/1243) was an Ismaili poet. Born near Qazvīn, he was alive when Imam Ḥasan of Alamūt (d. 561/1166) proclaimed his doctrine of qiyāmat or spiritual 'resurrection' in 559/1164. He was a secretary of the governor of the fortress of Gird Kūh, Shihāb al-Dīn, whom he later followed to Quhistān. Around 630/1232 he was in Alamūt, preparing a copy of the diwan whose surviving fragments are published here, to be offered to the Imam of the Ismailis at the time, ʿAlāʾ al-Dīn Muḥammad (d. 653/1255). Ḥasan Maḥmūd was well-versed in the intellectual and spiritual universe of Nizārī Ismailism as recorded, inter alia, in Naṣīr al-Dīn Ṭūsī's (d. 672/1274) Rawḍa-yi taslīm , Sayr wa sulūk , and Āghāz wa anjām . The present diwan contains the most complete contemporary catalogue of the terminology used in expressing Nizārī Ismaili doctrine, surpassing even the works of Ṭūsī, Nāṣir Khusraw (d. after 462/1070) and Nizārī Quhistānī (d. 720/1320)